Navigating risk factors and interventions on early-onset attention deficit hyperactivity disorder: A case report - Tristan, Christopher Daniel; Rahman, Awalil Rifqi Kurnia; Kurniawan, Avenetus Immanuel Gifta; Anggriawan, Fatkan Hidayat; Bangun, Susi Rutmalem (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental illness primarily affecting children. The peak onset age for ADHD is around 7.5 years with early-onset ADHD linked with worse clinical outcomes if not properly managed. We reported a 3-year-old girl presented with symptoms including self-harm, aggression toward her sibling and peers, hyperactivity, inability to focus, and distractibility. The patient had a history of post-term birth and oligohydramnios, and her symptoms were exacerbated by reduced maternal care, limited parental care, and inconsistent-lacked firmness parenting style. A multiaxial evaluation confirmed the diagnosis of ADHD, supported by Skala Penilaian Perilaku Anak Hiperaktif Indonesia (SPPAHI) score. The patient received a comprehensive non-pharmacological intervention, including applied behavior analysis (ABA) therapy with a discrete trial training (DTT) approach, family therapy to address parenting dynamics, and occupational and speech therapy to target fine motor and language delay. At 6-month follow-up, significant improvements were observed in behavior, attention, and total quality of life. This case highlights the complex interplay of genetic disorders, maternal stress, post-term birth, pregnancy-related complications, and problematic family dynamics in early-onset ADHD. Therapeutic management in early-onset ADHD must emphasize behavioral and family-focused therapies with DTT and family therapy proving effectiveness, while pharmacological treatment is considered as a last resort.